2020
DOI: 10.12928/telkomnika.v18i6.16466
|View full text |Cite
|
Sign up to set email alerts
|

A modified Cuk DC-DC converter for DC microgrid systems

Abstract: A new efficient step-up direct current-direct current (DC-DC) power converter that is suitable for DC microgrid systems is proposed in this paper. The proposed step-up DC-DC converter is derived from the conventional Cuk DC-DC power converter. Output voltage analysis that is useful to predict the conduction losses is presented. It is shown that the proposed step-up DC-DC converter is more efficient than the conventional DC-DC boost power converter. Current ripple analysis that is useful to determine the requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Dahono et al [43], Dahono and Dahono [44], have shown that the conventional Cuk converter can be modified into the one shown in Figure 2. As it is derived from convensional topology of the Cuk DC-DC converter, this converter has very low ripple contents in the input and output sides.…”
Section: New Family Of Dc-dc Power Converters 21 Single-phase Modifie...mentioning
confidence: 99%
See 1 more Smart Citation
“…Dahono et al [43], Dahono and Dahono [44], have shown that the conventional Cuk converter can be modified into the one shown in Figure 2. As it is derived from convensional topology of the Cuk DC-DC converter, this converter has very low ripple contents in the input and output sides.…”
Section: New Family Of Dc-dc Power Converters 21 Single-phase Modifie...mentioning
confidence: 99%
“…A very low input current ripple is desirable in most of the applications such as photovoltaic and fuel cell power generation systems. In recent papers, the authors have proposed the modified Cuk DC-DC converter [43], [44]. This modified Cuk DC-DC converter can be step-down as a DC-DC buck converter or also can be step-up as a DC-DC boost converter.…”
Section: Introductionmentioning
confidence: 99%
“…This unique combination gives SEPIC converters a key advantage over traditional buck-boost converters: The input and output voltages are kept in phase. In addition, the SEPIC responds to a short-circuit output with greater grace since it uses a series capacitor to move energy from the input to the output 21 – 28 . Another advantage of SEPIC converters is their ability to shut down completely.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 Conventional single-phase inverter Several solutions have been proposed to resolve the aforementioned problems using DC-DC converters other than a simple buck type [18][19][20][21][22][23] . The inverter in Ref.…”
Section: Introductionmentioning
confidence: 99%